INFLUENCE OF OPEN AND SEALED FRACTURES ON FLUID FLOW AND WATER SATURATION IN SANDSTONE CORES USING MAGNETIC RESONANCE IMAGING - Baraka-Lokmane S.; Teutsch G.; Main I.G. (My University, 2001)
We use Magnetic Resonance Imaging (MRI) to image the imbibition of water by capillary action in a right-cylindrical sample of a porous sedimentary rock with low iron content. In the method some 55 repeat images are taken over a period of approximately two hours, covering five vertical sections. The evolution of the water flood front and the degree of water saturation can be observed by examining snapshots of proton density. The results clearly show (a) the development of a rising wetting front in the rock matrix (b) preferential flow along open fractures observed on the core surface, and (c) reduced flow associated with sealed fractures. The inferred location, orientation and connectivity of conducting and sealing fractures are confirmed by impregnating the sample after the test with an appropriate low-viscosity setting resin and taking serial thin sections in destructive mode. The results validate the utility of MRI as a non-destructive analytical tool for visualizing the distribution of water inside fractured porous media with low iron content. The technique identifies paths of high and low permeability in the sample, and quantifies the fracture location, orientation, and connectivity in sedimentary rocks. Preferential fluid flow in open fractures during capillary imbibition implies that the fractures are more water-wet than the clasts within the matrix. This may be due to due to differences in the age, morphology and mineral structure on the surface of the pores and the fractures.
Keywords: FRACTURE GEOMETRY; MRI; WATER SATURATION